1986
DOI: 10.1264/microbes1986.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle of <i>Peridinium</i> sp. B3 (Dinophyceae) Isolated from Lake Begnas, Nepal

Abstract: Abstract:Encystment and excystment in the life cycle of a dinoflagellate Peridinium sp. B3, which was isolated from Lake Begnas in the Pokhara Valley, Nepal, were investigated by use of a clonal population.The maximum cell concentration was 3103 vegetative cellsml-1 in BL medium after about 4 weeks at 30C.Sexual reproduction of the cells was induced after the cells in late logarithmic phase were inoculated into nitrogen and phosphorous deficient medium, and also was spontaneously induced in BL medium.Sexual re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
2
3
0
Order By: Relevance
“…The small cysts are apparently asexual but the large cysts are probably sexual as they are larger than the vegetative cells (19.7 vs 15.6 μm). Small potential gametes were observed as reported previously (Pfiester et al, 1984;Sako et al, 1986) although sexual fusion was not observed. Sexual cysts were generated by Parvodinium inconspicuum in culture (Pfiester et al, 1984), but not detailed in Parvodinium umbonatum (Zhang et al, 2011).Cysts of Johsia chumphonensis differ from those of P. umbonatum and P. inconspicuum in that they are rounded, not pyriform to ovoid (Chu et al, 2008;Tardio et al, 2009).…”
Section: Coccoid Cells Were Observed In Cultures Ofsupporting
confidence: 79%
See 1 more Smart Citation
“…The small cysts are apparently asexual but the large cysts are probably sexual as they are larger than the vegetative cells (19.7 vs 15.6 μm). Small potential gametes were observed as reported previously (Pfiester et al, 1984;Sako et al, 1986) although sexual fusion was not observed. Sexual cysts were generated by Parvodinium inconspicuum in culture (Pfiester et al, 1984), but not detailed in Parvodinium umbonatum (Zhang et al, 2011).Cysts of Johsia chumphonensis differ from those of P. umbonatum and P. inconspicuum in that they are rounded, not pyriform to ovoid (Chu et al, 2008;Tardio et al, 2009).…”
Section: Coccoid Cells Were Observed In Cultures Ofsupporting
confidence: 79%
“…The life cycle of Johsia chumphonensis appears complex. Johsia chumphonensis shed the theca through the hypothecal opening and binary division occurs outside the theca, as also reported in an unidentified Parvodinium species (Sako et al, 1986) and Peridinium sanguineum H.J.Carter (Pfiester & Anderson, 1987). It is interesting to note that J. chumphonensis generate two kinds of coccoid cells in cultures differing in the size and wall thickness.…”
Section: Coccoid Cells Were Observed In Cultures Ofsupporting
confidence: 66%
“…Gametes of various dinoflagellate species are distinctive from vegetative cells in their reduced number of chloroplasts per cell and smaller size (Kita et al 1993, Pfiester 1975, 1977, Sako et al 1984, 1986. The male gametes of Pyrophacus steinii are different from the female gametes and the vegetative cells in their smaller size, round shape and fewer thecal plate number.…”
Section: Discussionmentioning
confidence: 99%
“…Sexual reproduction in dinoflagellates is difficult to recognize because gametes usually look similar to vegetative cells and cell fusion can be confused with division (Pfiester & Anderson, 1987). Nevertheless, sexual cyst formation has been reported for more than 20 dinoflagellate species (Sako et al. , 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Sexual reproduction in dinoflagellates is difficult to recognize because gametes usually look similar to vegetative cells and cell fusion can be confused with division (Pfiester & Anderson, 1987). Nevertheless, sexual cyst formation has been reported for more than 20 dinoflagellate species (Sako et al, 1986). In this process haploid vegetative dinoflagellate cells produce gametes, pairs of gametes fuse producing a planozygote that loses motility and develops into a hypnozygote cyst.…”
Section: Introductionmentioning
confidence: 99%